Increased miR-223-3p in Leukocytes Positively Correlated with IL-17A in Plasma of Asthmatic Patients - Wenjuan Xu (Iranian Journal of Allergy, Asthma and Immunology, 2020)
Asthma is a common airway inflammation with an intricate underlying mechanism. The role played by circulating miRNAs in asthma remains unclear. In the present study, we aimed to investigate the role of miR-223-3p in leukocytes of asthma and identify the relationship between miR-223-3p and inflammatory cytokines in asthma. Using real-time polymerase chain reaction (RT-PCR), we detected miR-223-3p expression in peripheral blood leukocytes from 23 asthmatic patients and 20 healthy controls. The levels of IFN-γ (Th1 cytokine), IL-4 (Th2 cytokine), IL-17A (Th17 cytokine) in plasma were examined using enzyme-linked immunosorbent assay (ELISA). Analysis of variance (ANOVA) and Spearman’s test was used for statistical analysis. The expression of miR-223-3p in peripheral blood leukocytes was upregulated in the asthmatic patients compared with that in the healthy controls. Increased miR-223-3p expression was associated with forced expiratory volume in 1-second percent predicted (FEV1% predicted). A positive correlation was noted between miR-223-3p and IL-17A. The findings of this study showed that miR-223-3p plays a vital role in the pathogenesis of asthma and can serve as a novel biomarker for asthma.